Ergonomics for beginners : a quick reference guide. - Dul, Jan, 1954-; Weerdmeester, Bernard, ....- (Boca Raton : CRC, 2008)
1 Introduction What is ergonomics? What is an ergonomist? Social significance of ergonomics General and individual ergonomics 2 Posture and movement Biomechanical, physiological and anthropometric background Posture Movement 3 Information and operation The user Information Controls Relationship between information and operation 4 Environmental factors Noise Vibration Illumination Climate Chemical substances 5 Work organization, jobs and tasks Tasks Jobs Work organization 6 The ergonomic approach Project management 7 Sources of additional information Bibliography Useful websites Index
Keywords: Ergonomie